Pendidikan Karakter Holistik di Era Disrupsi: Mengintegrasikan Konsep Tazkiyatun Nafs Imam Al-Ghazali - Muhammad Hasyim (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2022)
This study aims to analyze the concept of tazkiyatun nafs (purification of the soul) according to Imam Al-Ghazali and its relevance in the development of holistic character education in the era of disruption. This study uses a literature review method by analyzing relevant literature, such as books, scientific journals, and related articles. The results of the study show that the concept of tazkiyatun nafs has significant relevance in answering the challenges of character education in the era of disruption. Tazkiyatun nafs values, such as honesty, integrity, compassion, and concern for others, can be a solid foundation in shaping the character of students who have noble character, integrity, and have mental resilience in the face of rapid changes in the times. This study recommends the integration of tazkiyatun nafs values into the curriculum, the development of innovative learning methods, strengthening the role of teachers as role models, the involvement of parents and the community, and the wise use of technology in character education